Dellmann's textbook of veterinary histology - Eurell, Jo Ann (Blackwell Publishing, 2006)
The Sixth Edition focuses on the most current knowledge of cell, tissue and organ structure and function. All information has been fully revised and updated by the authors, both experts in their fields. Written with first year veterinary students in mind, it is also an important resource for veterinarians, graduate students, and others who require information on animal tissue structure and function.